Hubungan antara Kecerdasan Emosional dengan Prestasi Belajar Siswa Kelas II SMA Negeri 2 Mataram - Bahtiar Bahtiar (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
From a recent research in psychology, revealed that IQ is not only factor that affect learning performance. One of other factor is emotional intelligence (EQ). This article explore the relation between EQ and learning performance, based on survey at 2ndÂ grade State High school (SMAN 2) Mataram. Emotional intelligence is oneâ€™s capability to recognize and manage emotion, self-motivation, recognize others emotion (empathy), and ability to build relation (cooperation) with others. Learning performance is learning outcome from learning activity that measured and rated academically at report figure. SQ scale used here based on Daniel Goleman theory. The result is that there are relation between emotional intelligence and learning performance.Â